Interlaboratory Validation of Toxicity Testing Using the Duckweed Lemna minor Root-Regrowth Test - Jihae Park; Eun-Jin Yoo; Kisik Shin; Stephen Depuydt; Wei Li; Klaus-J. Appenroth; Adam D. Lillicrap; Li Xie; Hojun Lee; Geehyoung Kim; Jonas De Saeger; Soyeon Choi; et al. (Biology, 2021)
The common duckweed (Lemna minor), a freshwater monocot that floats on the surfaces of slow-moving streams and ponds, is commonly used in toxicity testing. The novel Lemna root- regrowth test is a toxicity test performed in replicate test vessels (24-well plates), each containing 3 mL test solution and a 2–3 frond colony. Prior to exposure, roots are excised from the plant, and newly developed roots are measured after 3 days of regrowth. Compared to the three internationally standardized methods, this bioassay is faster (72 h), simpler, more convenient (requiring only a 3-mL) and cheaper. The sensitivity of root regrowth to 3,5-dichlorophenol was statistically the same as using the conventional ISO test method. The results of interlaboratory comparison tests conducted by 10 international institutes showed 21.3% repeatability and 27.2% reproducibility for CuSO4 and 21.28% repeatability and 18.6% reproducibility for wastewater. These validity criteria are well within the generally accepted levels of <30% to 40%, confirming that this test method is acceptable as a standardized biological test and can be used as a regulatory tool. The Lemna root regrowth test complements the lengthier conventional protocols and is suitable for rapid screening of wastewater and priority substances spikes in natural waters.